PECULIARITY OF COVERAGE OF MILITARY CONFLICTS IN HISTORICAL RETROSPECT - Літинська, Юлія (Modern engineering and innovative technologies, 2024)
The paper examines a historical retrospective of the coverage of military conflicts by audiovisual media. The socio-political and technological factors that influenced the change in the methods of media coverage of wars are analyzed, as well as their impo